Transformasi Kelembagaan KPK: UU KPK Sebagai Kebijakan Pencegahan Korupsi di Indonesia - BAYU, CHANDRA; BAYU, CHANDRA (Jurnal Dinamika Sosial Budaya, 2021)
This article questions "How is the institutional transformation of the KPK after the revision of the KPK Law in supporting corruption prevention policies in Indonesia?". The purpose of writing this article is to trace the extent to which the KPK institutional transformation after the revision of the KPK Law in supporting corruption prevention policies in Indonesia is based on a comprehensive rational model. This needs to be done because the insignificant decrease in corruption cases in Indonesia is inseparable from the institutional factors of the KPK which have tended to be oriented towards eradication, are less effective and efficient in supporting corruption prevention policies. From this analysis it can be said that the institutional transformation of the KPK in the revision of the KPK Law, which was originally a superpower / superbody institution where the concentration of power tends to be corrupt, became a state institution in the executive power clump, was carried out as a form of legal reform as well as upholding an anti-corruption ethical commitment to prevent and eradicate acts. The criminal act of corruption is effective, efficient and integrated / synergistic, which is the most rational policy for the state.Keywords: Transformation, Institution, KPK, Policy, Legal Reform.
Keywords: Transformation; Institution; KPK; Policy; Legal Reform.